Predictors of survival in paediatric mitral valve surgery: the impact of age at operation at late follow-up. (23rd March 2022) - Brancaccio, Gianluca; Trezzi, Matteo; Croci, Ileana; Guerra, Giulia; Chinali, Marcello; Grandinetti, Maria; Perri, Gianluigi; D'Anna, Carolina; Iodice, Francesca; Giorni, Chiara; Iacobelli, Roberta; Galletti, Lorenzo
Abstract: OBJECTIVES: The aim of this study was to elucidate predictors of death and reintervention after mitral valve (MV) surgery in children. METHODS: A single-centre retrospective study was performed enrolling 142 patients younger than 18 years who underwent primary index surgical mitral repair or replacement at Bambino Gesù Children's Hospital in Rome from July 1982 to April 2020. Patients with complete, transitional or partial atrioventricular septal defect and patients with single ventricle physiology were excluded. Patients were stratified according to the age group: group 1 (<1 year old), group 2 (1–5 years old) and group 3 (>5 years old). The composite primary outcome was freedom from death or transplant. The secondary outcome was freedom from redo MV surgery. RESULTS: Transplant-free survival was 89% at 5 years and 88% at 10 years. Stratified by age, group 1 had poorer outcome in comparison with other groups (log-rank test P = 0.105). Both univariate and multivariate analyses showed that age <1 year was a significant risk factor for death or transplant ( P = 0.044). Age <1 year was associated with increased risk of reoperation (aHR = 3.38, P = 0.009), while the presence of genetic syndrome (aHR = 0.22) and preoperative EF% (aHR = 0.97) were protective factors for reoperation. CONCLUSIONS: The overall survival and freedom from reoperation in children undergoing MV surgery still need improvements. Younger age was a significant risk factor for death and reintervention both after repair and replacement of the MV. In particular, infants and neonates have a three-fold risk for death compared to children. Abstract : The surgical approach to mitral valve (MV) dysfunction in the paediatric population has not changed much in over 20 years except for interventional procedures and the recent use of expandable tissue valves [1–5].